Measurement of Microscopic Deformations Using Double-Exposure Holographic Interferometry and the Fourier Transform Method - Almoro, Percival; Daza, Marlon Rosendo (Science Diliman: A Journal of Pure and Applied Sciences; Vol 10 No 2 (1998), 2007)
Microscopic deformations on the surface of a circular diaphragm were measured using double exposure holographic interferometry and Fourier transform method (FTM). The three-dimensional surface deformations were successfully visualized by applying FTM to holographic interferogram analysis. The minimum surface displacement measured was 0.317 µm. This was calibrated via the Michelson interferometry technique.
Keywords: holographic interferometry, microscopic deformation measurement, Fourier transfonn method, double-exposure method, hologram, laser application